Studia nad domieszką mineralną w ceramice naczyniowej kultury amfor kulistych z terenu Kujaw - Świerczyńska, Anna Maria (Folia Praehistorica Posnaniensia, 2019)
This article relates to the question, „what exactly is a mineral admixture in Globular Amphora Culture?”. My studies prove that only the granites fulfill the criteria. I designed the experiment. One of the goals was to examine which stone is the easiest to process. It was a rapakivi granite. Its minerals are pink or grey after processing. The admixture found in GAC ceramics has the same color and the same size of minerals. There was another type of admixture which was not recognizable.